Prime-Boost Vaccine Regimen for SjTPI and SjC23 Schistosome Vaccines, Increases Efficacy in Water Buffalo in a Field Trial in China - Da'Dara, Akram A.; Li, Changlin; Yu, Xinling; Zheng, Mao; Zhou, Jie; Shollenberger, Lisa M.; Li, Yue-sheng; Harn, Donald A. (Frontiers in Immunology, 2019)
Schistosomiasis remains a serious zoonotic disease in China and the Philippines. Water buffalo and cattle account for the majority of transmission. Vaccination of water buffalo is considered a key strategy to reduce disease prevalence. Previously, we showed that vaccination of water buffalo with SjC23 or SjCTPI plasmid DNA vaccines, induced 50% efficacy to challenge infection. Here, we evaluated several parameters to determine if we can develop a two dose vaccine that maintains the efficacy of the three dose vaccine. We performed four trials evaluating: (1) lab produced vs. GLP grade vaccines, (2) varying the time between prime and boost, (3) the influence of an IL-12 adjuvant, and (4) a two dose heterologous (DNA-protein) prime-boost. We found the source of the DNA vaccines did not matter, nor did increasing the interval between prime and boost. Elimination of the IL-12 plasmid lowered homologous DNA-DNA vaccine efficacy. A major finding was that the heterologous prime boost improved vaccine efficacy, with the prime-boost regimen incorporating both antigens providing a 55% reduction in adult worms and 53% reduction in liver eggs. Vaccinated buffalo produced vaccine-specific antibody responses. These trials suggest that highly effective vaccination against schistosomes can be achieved using a two dose regimen. No adjuvants were used with the protein boost, and the potential that addition of adjuvant to the protein boost to further increase efficacy should be evaluated. These results suggest that use of these two schistosome vaccines can be part of an integrated control strategy to reduce transmission of schistosomiasis in Asia.